Chemical Constituents and Bioactivity Studies of Two Polytrichaceae Species, Polytrichum formosum Hedw. and Polytrichum commune Hedw. - Onur Tolga Okan (BioResources)
This study aimed to assess the chemical composition, specifically metal content, phenolics, and fatty acids, of two bryophyte species, Polytrichum formosum and Polytrichum commune, which belong to the Polytrichaceae family. The bioactivities of these species were also evaluated. Microwave plasma atomic emission spectroscopy was used to analyze 13 elements, revealing the presence of 10 elements at varying concentrations in both species. Iron (Fe) was the most prominent element in P. formosum, with a concentration of 7610 mg/kg, whereas calcium (Ca) was the most prominent element in P. commune, at a concentration of 8430 mg/kg. The high-performance liquid chromatography mass spectrometry analysis revealed the presence of 53 phenolic compounds, with quinic acid, protocatechuic acid, and fisetin being the most prominent with concentrations of 4.45, 2.26, and 1.46 mg analyte/g extract, respectively. When evaluated for total phenolic content, P. commune had a higher concentration of phenolic compounds than P. formosum. The fatty acid profile obtained via gas chromatography-mass spectrometry analysis revealed higher concentrations of oleic acid (36.6% for P. formosum and 38.0% for P. commune) and palmitic acid (35.5% for P. formosum and 33.8% for P. commune). Three independent assays assessed the antioxidant capacities of both plants, which revealed significant antioxidant potential in both species.